Implementation Of Marketing Programs In Competitive Strategies In The Television Industry Based On Service Dominant Logic And Value Co-Creation - Robbiah Adawiyah; Endy Gunanto Marsasi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Digitization has had a significant impact in the television sector in Indonesia, changing people's media consumption patterns and putting significant pressure on the television industry. This study aims to analyze the marketing and competitive strategies of Nusantara TV, particularly through the development of the